Traffic control elements influence on accidents, mobility and the environment - Kinderytė-Poškienė, Jurgita; Sokolovskij, Edgar (Transport, 2008)
This paper presents the main traffic control elements, which were classified into groups. One group presents traffic control elements, which have different effects on accidents: reduce the number of accidents, do not have statistically significant effect on the number of accidents and those which appear to lead to an increased number of accidents. Next group presents traffic control elements, which have effect on mobility and the environment. Some of them can improve mobility on road, others reduce mobility on road. Presented elements, which are useful for the environment, are considered. First published online: 27 Oct 2010